e Influence of Digital Marketing MSME Food Product on Consumer Repurchase Intention in Sukabumi West Java - Tommy Agus Darmawan; Rindang Matoati (Universitas Sultan Ageng Tirtayasa, 2022)
Internet users nowadays increase from time to time, COVID-19 pandemic make people get used to it with all of daily activities become digital. Therefore people must be able to keep up with the growth of the internet in all aspect, for example in marketing field. The purpose of this research is for analyze the influence of the digital marketing food product MSME on repurchase intention consumer in Sukabumi West Java, with expectation that MSME actors in Sukabumi have a desire to keep growing in digital marketing. There were 126 respondents in this study. The data analysis method in this study was descriptive analysis and multiple linear regression analysis with IBM SPSS 25 software. The result in this study is digital marketing have a positive effect on consumer purchase intention in Sukabumi, with all four independent variable has a significant effect that is consumer expectation, marketing factors, service factors, and functional factors.